Volume 7: Ocean Space Utilization; Professor Emeritus J. Randolph Paulling Honoring Symposium on Ocean Technology 2014
DOI: 10.1115/omae2014-23835
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Asymmetric FPSO Roll Using a Frequency Domain Method

Abstract: FPSO roll prediction has traditionally been performed assuming symmetric roll damping resulting in identical roll responses from portside and starboard waves. Recent interest in the industry to predict asymmetric roll response, either due to asymmetric mooring and riser configurations or damping devices, has led to the development of time domain models utilizing asymmetric Morison drag elements. Here, a frequency domain methodology has been developed to account for asymmetric bilge keels leading to differing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For an FPSO with both truncated bilge keel and asymmetric risers, the two asymmetric effects can be at opposite side, acting against each other. Studies by Tom et al [6], Seah et al [7] and Bigot et al [8] suggested that the effect of asymmetric bilge keel is mainly due to quadratic damping. Rezende et al [9] claimed that the inertia effect of asymmetric risers is insignificant in their study, and simplified the riser effect using Morrison element.…”
Section: The Effect Of Truncated Bilge Keel With Asymmetric Risersmentioning
confidence: 99%
See 3 more Smart Citations
“…For an FPSO with both truncated bilge keel and asymmetric risers, the two asymmetric effects can be at opposite side, acting against each other. Studies by Tom et al [6], Seah et al [7] and Bigot et al [8] suggested that the effect of asymmetric bilge keel is mainly due to quadratic damping. Rezende et al [9] claimed that the inertia effect of asymmetric risers is insignificant in their study, and simplified the riser effect using Morrison element.…”
Section: The Effect Of Truncated Bilge Keel With Asymmetric Risersmentioning
confidence: 99%
“…In the present work, the method similar to Bigot et al [8] is applied to simulate bilge keel in frequency domain, with constant drag coefficient. The drag force on a bilge keel, bk F , which is normal to the bilge keel, is given by the Morrison drag formula, 0.5…”
Section: R Bk Bk Bk H = H + H (11)mentioning
confidence: 99%
See 2 more Smart Citations